Long-Term Sequelae of COVID-19: A Review - Orzeł, Jakub; Skowron, Aleksandra; Pelczar, Patrycja; Przygoda, Aleksandra (Quality in Sport, 2026)
Introduction. Long COVID (post-COVID-19 syndrome) is defined as a constellation of symptoms persisting or emerging at least three months after acute SARS-CoV-2 infection, lasting for a minimum of two months and not explained by an alternative diagnosis. It affects millions of patients worldwide regardless of the severity of primary infection, and its underlying pathophysiology remains incompletely understood. Aim. The aim of this review is to summarize the current state of knowledge on Long COVID syndrome, with a particular focus on its clinical manifestations across multiple organ systems, underlying pathophysiological mechanisms, and long-term consequences in both adult and pediatric populations. Methodology. A review of the literature was conducted through a systematic search of the PubMed database using the keywords: "Long COVID", "post-COVID syndrome", "post-acute sequelae of SARS-CoV-2", "PASC". Publications from 2020 to 2026 were included. Results. Long COVID affects multiple organ system. The most common symptoms are neurological, including fatigue, brain fog and memory impairment. Cardiovascular complications include POTS, myocarditis, arrhythmias and thromboembolic events. Pulmonary sequelae are common even after a mild course of the disease. Other documented complications include renal dysfunction, female fertility disorders and paediatric post-COVID syndrome. Immunological mechanisms appear to play a key role in the pathogenesis of the syndrome. Conclusions. Long COVID is a multisystemic and complex condition requiring a holistic diagnostic and therapeutic approach. There are currently no reliable biomarkers or targeted therapies. It poses a serious public health problem, and further research is needed to improve treatment outcomes.